A new optimization approach to improve the overall performance of thick wind turbine airfoils. (1st December 2016) - Li, Xingxing; Yang, Ke; Bai, Jingyan; Xu, Jianzhong
Abstract: A crucial problem of designing thick airfoils is balancing structural and aerodynamic requirements. This paper documented a new idea to deal with the thick airfoil's design. Firstly, the relative thickness of the original airfoil was increased to enhance its structural property. Then the overall aerodynamic performance was improved by the optimization design method. Specifically, this paper put forward a mathematical model of the overall optimization employing airfoil's performance evaluation indicators which represent modern rotor blades' aerodynamic requirements of "high efficiency, low extreme load, wide range of operating angle of attack and stability with varying operating conditions". Based on this model, an integrated optimization platform for thick airfoils' overall design was established. Through an optimization experiment, a new 35-percent relative thickness airfoil was obtained. The new airfoil was predicted with high design lift coefficient, acceptable maximum lift to drag ratio, moderate stall parameter, and desirable stability parameters. These characteristics contribute to a high overall performance which could be competent with commonly used thick DU airfoils. Lift characteristics of the new airfoil have been validated by tests. These results confirmed the proposed method has effectively balanced airfoil's complicated requirements and successfully improved the new airfoil's overall performance. Highlights: An optimization method to improve performance of scaled thick airfoil is proposed. The design focuses on the overall performance based on the blade's requirement. Airfoils' performance evaluation indicators is employed to orient the overall design. Genetic algorithm is employed to deal with optimization of multi-design-objective. Achievement of the desirable airfoil validates the proposed method.